Estimates of Healthcare Spending for Preterm and Low-Birthweight Infants in a Commercially Insured Population: 2008–2016. Issue 12 (December 2020) - Beam, Andrew L.; Fried, Inbar; Palmer, Nathan; Agniel, Denis; Brat, Gabriel; Fox, Kathe; Kohane, Isaac; Sinaiko, Anna; Zupancic, John A. F.; Armstrong, Joanne
Abstract : (Abstracted from J Perinatol 2020;40:1091–1099) Preterm birth and low birthweight incur large medical, social, and economic costs on affected families and the US health care system. A 2007 study from the Institute of Medicine estimated that the total cost associated with preterm delivery in the United States was at least $26.2 billion annually or $51, 600 per infant born preterm.